VALIDITAS PERANGKAT PEMBELAJARAN BERORIENTASI MODEL PEMBELAJARAN “SMART” PADA MATERI SISTEM PENCERNAAN MANUSIA UNTUK MELATIH KEMAMPUAN BERPIKIR SISWA SMP - Sriwulandari Duengo; Masra Latjompoh; Mustamin Ibrahim (Fakultas MIPA Universitas Negeri Gorontalo, 2020)
This research aims to describe the validity of learning tool that is oriented learning method “SMART” on material of human digestion system to train students’ thinking ability of junior high school 3 Paguyaman. This is a research development model. Products developed are in the form of Lesson Plan and LKPD on the material of human digestion for 8th grade of junior high school using SMART learning model. The results of the study show that learning tool development has valid criteria. The results of lesson plan validation by expert obtained a percentage score ranging from 91.5% to 100% while for LKP obtained a percentage score around 83.25% to 100%. Based on the results of the study, it can be concluded that the learning tool oriented SMART learning model on the material of the human digestive system meets valid criteria because it is based on the results of expert validation and is suitable for use in learning for students of public junior high school 3 Paguyaman. Keywords: Validity, SMART learning, Learning tools, Digestive system